Development and validation of PART (Pharmacotherapy Assessment in Renal Transplant Patients) criteria to assess drug‐related problems in an outpatient renal transplant population: A cross‐sectional study. Issue 1 (15th January 2019) - El Raichani, Layal; Du, Qian; Mathieu, Alexandre; Almassy, Sabrina; Lalonde, Lyne; Berbiche, Djamal; Gélinas‐Lemay, Elisabeth; Boudreau, Nathalie; Cardinal, Héloïse
Abstract: Kidney transplant recipients are at risk of pharmacological interactions and adverse drug reactions. Community pharmacists are uniquely poised to detect and intervene in cases of drug‐related problems. The aims of this study were to develop and validate a list of explicit criteria to be used by community pharmacists to assess drug‐related problems in kidney transplant patients, and to assess their frequency and their determinants. First, we used a modified RAND method where a panel of experts established the PART (Pharmacotherapy Assessment in Renal Transplant Patient) criteria. Then, we performed a cross‐sectional study in which we applied the PART criteria to 97 prevalent kidney transplant recipients followed at a single university‐affiliated center. The final list of PART criteria included 70 drug‐related problems and was reliable (kappa: 0.88). An average of 1.2 drug‐related problems per patient was detected when the PART criteria were applied, with 68% of patients having at least 1 problem. This figure was 1.4 per patient using the expert judgment of renal transplant pharmacists who had no access to the PART list. The total number of medications taken was the only factor associated with the number of drug‐related problems (β: 0.27 for an increase of five medications, 95% CI 0.005, 0.547). The PART criteria provide a novel tool for community pharmacists to systematically detect drug‐related problems in kidney transplant recipients.